Fluorine-functionalized and simultaneously reduced graphene oxide as a novel hole transporting layer for highly efficient and stable organic photovoltaic cells - Kim, Su-Hyeon; Lee, Cheol-Ho; Yun, Jin-Mun; Noh, Yong-Jin; Kim, Seok-Soon; Lee, Sungho; Jo, Seung Mu; Joh, Han-Ik; Na, Seok-In (ROYAL SOC CHEMISTRY, 2014)
A one-step reduction and functionalization of graphene oxide (FrGO) was easily achieved using a novel phenylhydrazine-based reductant containing fluorine atoms, which can induce p-type doping due to its high electronegativity. The FrGO-based OPV exhibited a high power conversion efficiency of similar to 6.71% and a superior OPV-stability to commercial PEDOT:PSS.
Keywords: POLYMER SOLAR-CELLS; WATER